Reflexivity, ethics and accountability: facilitators working for gender transformation with boys and men. Issue 3 (3rd April 2023) - Keddie, Amanda; Lees, David; Delaney, Maria
ABSTRACT: Increased attention to gendered violence has led to a burgeoning of different community-based programmes designed to support men and boys to adopt more inclusive and respectful masculinities. Accompanying this attention has been a proliferation of guidance materials to support facilitators to critically reflect on their identities and practice to enact their work in gender just ways. In this paper, we explore issues of reflexivity, ethics and accountability in how facilitators work with men and boys. Through three facilitator stories, we consider processes of reflexivity in relation to facilitators: 1) recognizing their intersectional selves, 2) acknowledging and learning from prejudice, and 3) bringing an ethics of openness and vulnerability to their work. We argue that these areas of reflexivity are central to gender transformative facilitation.